The influence of premenopausal hysterectomy on bone mineral density - Abdulwahab, Dalia F; Al- Baldawy, Reyad; Chabek, Mohammed; Awang, Mokhtar; Abd. Wahab, Noraziana; Al-Kubaisi, Muna Khaleel Dheyab (2012)
Objective: To investigate whether premenopausal hysterectomy has an effect on bone mass in women in their fifties . Methods: This cross-sectional study was performed on 25 healthy women who had premenopausal hysterectomy before the age of 45 and at least 2 years before the study with 40 healthy natural postmenopausal women 45–60 years old. Evaluation of the menopausal state was done by measuring serum follicular stimulating hormone and serum estradiol. Bone mineral density of the left proximal femur was determined by dual energy X-ray absorptiometry in six regions (femoral neck, greater trochanter, interochantric, ward‘s triangle, shaft, total hip region). Evaluation of bone remodeling done by measuring serum alkaline phosphotase. The result of both groups were compared. Results: The study showed slight increment of BMD among cases with hysterectomy than the control group by an amount ranging between 1.9% in the femoral shaft to 4.8% in the greater trochanter and ward‘s triangle. These differences were not statistically significant and even when they were exceptionally significant as the case with BMD of the femoral neck and intertrochantric area they were too small in magnitude to be of clinical relevance. Conclusion: Hysterectomy had no impact on bone parameters even after adjusting for the duration of menopause.